Seven mechanisms of oxygen evolution reaction proposed recently: A mini review - Feng, Zihang; Dai, Chuanlin; Shi, Peng; Lei, Xuefei; Guo, Rui; Wang, Biao; Liu, Xuanwen; You, Junhua (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
•The Seven mechanisms of OER proposed recently have been summarized.•Some unique insights into the development of OER mechanisms have been provided.•More exploratory directions have been provided for the development of OER. The oxygen evolution reaction (OER) is a crucial step in the utilization and storage of sustainable energy. However, due to its multi-step and multi-electron transfer process, the kinetics of OER are extremely slow, limiting the development of these projects. Additionally, OER involves various reaction intermediates, which pose challenges for researchers to understand the mechanism of OER. Currently, some work is still focused on the traditional adsorbate evolution mechanism, which is not advanced and comprehensive enough, theoretically limiting the potential of these studies. Recent reports have proposed new mechanisms, and we have conducted a brief analysis of how they conceptualize the new mechanisms, demonstrate their feasibility, describe their operation, and detect them. We also put forward some relevant conclusions and prospects, hoping to provide more research perspectives and ideas for the development of OER.